Toe-brachial index is beyond a peripheral issue in patients with type 2 diabetes - Darban Hosseini Amirkhiz, Gisoo; Babaei, Mohammad Reza; Madani, Nahid Hashemi; Khamseh, Mohammad Ebrahim (PloS one, 2021)
Atherosclerosis is the leading cause of death in patients with diabetes. We aimed to evaluate the association between ankle-brachial index (ABI) and toe-brachial index (TBI) with carotid intima-media thickness (CIMT) in patients with type 2 diabetes (T2DM). This cross sectional study included 296 patients with T2DM who met the American Diabetes Association criteria for the assessment of peripheral arterial atherosclerosis. The ABI [less than or equal to] 0.9 and TBI [less than or equal to] 0.7 were considered as abnormal values. Linear and logistic regression analyses were performed to evaluate the association between TBI/ABI and CIMT. Right CIMT was significantly greater in the low TBI group (p = 0.03) while, left CIMT did not show a significant difference. Each 0.1-unit decrease in TBI value was independently associated with 0.017 mm increase in the right CIMT ([beta] ± SE; -0.017 ± 0.005, p = 0.002) and with odds of the presence of increased CIMT [odds ratio and 95% confidence interval: 1.21 (1.02, 1.44)] after adjustment with all traditional risk factors. There was not any significant association between ABI and increased CIMT. Beyond a suitable tool for the diagnosis of peripheral artery disease in patients with T2DM, TBI can be applied for prediction of subclinical carotid atherosclerosis.